2012
DOI: 10.1007/s13277-012-0628-4
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of IL-17-producing T cells is associated with regulatory T cell expansion and disease progression in chronic lymphocytic leukemia

Abstract: Little is known about the immunobiology of interleukin-17 (IL-17)-producing T cells and regulatory T cells (Treg) in chronic lymphocytic leukemia (CLL). In this study, the frequencies of Th17, Tc17, and CD39(+) Treg cells were enumerated in peripheral T cells isolated from 40 CLL patients and 15 normal subjects by flow cytometry. Our results showed a lower frequency of Th17 and Tc17 cells in progressive (0.99 ± 0.12 % of total CD3(+)CD4(+) cells; 0.44 ± 0.09 % of total CD8(+) cells) compared to indolent patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 64 publications
3
51
1
Order By: Relevance
“…Moreover, we found that reduced frequency of Th17 cells was associated with unmutated IGHV, which implied the protective role of Th17 cells in CLL. However, we observed any association between the number of IL-17 producing T cells and other prognosis markers such as CD38 or ZAP-70 expression [94]. It has recently been demonstrated that the frequency of IL-17 producing follicular Th cells was increased in CLL patients and correlated with advanced CLL stages [95].…”
Section: Th17 Cells In Cllcontrasting
confidence: 67%
See 1 more Smart Citation
“…Moreover, we found that reduced frequency of Th17 cells was associated with unmutated IGHV, which implied the protective role of Th17 cells in CLL. However, we observed any association between the number of IL-17 producing T cells and other prognosis markers such as CD38 or ZAP-70 expression [94]. It has recently been demonstrated that the frequency of IL-17 producing follicular Th cells was increased in CLL patients and correlated with advanced CLL stages [95].…”
Section: Th17 Cells In Cllcontrasting
confidence: 67%
“…On the other hand, cancer progression is supposed to be linked to Treg expansion and Th17 reduction [94]. The skewed balance between these cells may result in the burden of tissue inflammation, autoimmune diseases or cancer [46].…”
Section: The Skewed Balance Between Treg and Th17 In Cllmentioning
confidence: 99%
“…A shift in the balance between Th1, Th2, and Th17 immune subsets in CLL patients may also be an important factor in driving disease progression, and the T cell response in CLL patients is skewed toward Th2 polarization (11). Studies in CLL patients have also shown that a decrease in IL-17-producing T cells is associated with Treg cell expansion and disease progression (12)(13)(14), while increased Th17 cell numbers correlate with improved overall survival (15). To date, success in therapeutically enhancing cell-mediated immunity in CLL has been limited.…”
Section: Ibrutinib Treatment Increases Numbers Of Both Cd4mentioning
confidence: 99%
“…There is accumulating evidence that a Th17 response may play a role in CLL pathogenesis. Decreased frequency of Th17 cells has been found to be associated with Treg cell expansion and disease progression in CLL patients (12)(13)(14). In contrast, elevated Th17 cells in CLL patients is associated with improved survival (15).…”
Section: Ibrutinib Downregulates Immunosuppressive Molecules Cd200mentioning
confidence: 99%
“…27 Alternatively, in healthy individuals and patients with indolent Chronic Lymphocytic Leukemia (CLL), the frequency of IL-17 producing T cells was higher and inversely correlated with immunosuppressive T cells such as regulatory T cells (Tregs) which are found at relatively-higher frequency in progressive CLL patients. 28 This suggests that IL-17 may play a protective role in the pathogenesis of CLL. The frequency of IL-17 producing T cells was higher in mice with reduced tumor burden with primary intraocular B-cell lymphoma 29 and increased IL-17 in the tumor microenvironment was associated with improved clinical survival in patients with ovarian cancer.…”
Section: Ibrutinib-treated Dcs Promote An Il-17 Response Upon Culturementioning
confidence: 99%